(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
Inclusive education aims to provide equal learning opportunities for all students, including those with special educational needs. One of the major challenges in inclusive classrooms is ensuring active participation and engagement of all learners. This study explores the use of high-energy games as an effective pedagogical tool to promote active participation among children with special needs in inclusive settings. High-energy games are characterized by movement, interaction, and emotional involvement, which can enhance motivation and social integration. The research analyzes how such activities influence students’ engagement, communication skills, and overall learning experience.